Step frequency training improves running economy in well-trained female runners - Quinn, T. J.; Dempsey, S. L.; LaRoche, D. P.; Mackenzie, A. M.; Cook, S. B. (The Journal of Strength and Conditioning Research, 2021)
The purpose was to determine whether a short training program (15 minutes for 10 days) to increase step frequency to 180 steps per min would elicit improvements in running economy (RE). Experimental (n = 11) and control (n = 11) female subjects reported to the laboratory for 12 consecutive days and completed 2 RE tests at 3.4 and 3.8 m·s-1 (day 1 and 12), followed by a maximal oxygen uptake test (day 1 only), and experimental subjects completed a 10-day training program to increase step frequency (days 2-11). Control subjects completed the same runs without step frequency training. The training program consisted of running at 180 steps per minutes for 15 minutes at a self-selected velocity. A repeated-measures multivariate analysis of variance was used to test for differences. Oxygen consumption was significantly lower at each testing velocity for experimental but not control after the 10-day training program. The average drop in oxygen consumption across both speeds was approximately 11.0% (p < 0.05; mean Eta2p = 0.28). These lower oxygen consumptions were achieved at greater (7.0%) self-selected step frequencies (p < 0.01; mean Eta2p = 0.78), shorter (3.7%) step lengths (p < 0.05; mean Eta2p = 0.74), and lower (5.1%) heart rates (p < 0.05; mean Eta2p = 0.31) for experimental but not control. Training to run at a faster step cadence may be a viable technique to improve RE.